PENGUJIAN MEDIA TANAM DAN PUPUK ME-17 PADA PERTUMBUHAN BIBIT KAKAO - Muhammad Hatta (Jurnal Floratek, 2006)
Evaluation of Planting Media and Fertilizer Me-17 on Growth of Cacao Seedling ABSTRACTOne major issue on preparing seedling growth is planting media.  Soil as major media is frequently lack of nutrients for supporting long term of seedling growth.  Therefore, additional material and nutrients are needed to the soil.  The research objectives are to evaluate the best of composition of media and concentration of fertilizer Me-17 for the best growth of cacao seedling.  Result showed that three part of soil and one part of manure was the best mixture of  media for seedling growth. By using polynomial analysis, it was revealed that the best growth of seedling cacao was achieved at 3.05 to 3.67 cc/L of fertilizer Me-17.  However, no interaction between media and fertilizer Me-17 was existed.Keywords : cacao, Me-17, media, seedling